2001
DOI: 10.1046/j.1365-2141.2001.02551.x
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre, open, non‐comparative phase II study of a combination of fludarabine phosphate, cytarabine and granulocyte colony‐stimulating factor in relapsed and refractory acute myeloid leukaemia and de novo refractory anaemia with excess of blasts in transformation

Abstract: Summary. The primary objective of this study was to determine the complete remission (CR) rate achieved with the FLAG (fludarabine phosphate, cytarabine and granulocyte colony-stimulating factor) regimen in patients with relapsed or refractory acute myeloid leukaemia (AML) or de novo refractory anaemia with excess of blasts in transformation (RAEB-t). Secondary objectives were to evaluate survival and toxicity. Induction treatment consisted of between one and two courses of FLAG. Patients achieving CR received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
78
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 26 publications
8
78
0
2
Order By: Relevance
“…Recent interest has focused on the use of FLAG, with CR rates of up to 48% in patients with relapsed and refractory AML and de novo RAEB-t reported in a large series. 18 In patients with HR-ALL, the observed response rates of up to 67% with Ara-amsa are comparable to those reported with the use of multiphase reinduction salvage regimens in patients with relapsed or refractory ALL (62%). 19 Our remission rates are less impressive than those reported by Martino et al 20,21 (78% CR) with the use of a combination chemotherapy (intermediate-dose Ara-C, vindesine, mitoxantrone, cyclophosphamide, prednisolone and methotrexate).…”
Section: Discussionsupporting
confidence: 65%
“…Recent interest has focused on the use of FLAG, with CR rates of up to 48% in patients with relapsed and refractory AML and de novo RAEB-t reported in a large series. 18 In patients with HR-ALL, the observed response rates of up to 67% with Ara-amsa are comparable to those reported with the use of multiphase reinduction salvage regimens in patients with relapsed or refractory ALL (62%). 19 Our remission rates are less impressive than those reported by Martino et al 20,21 (78% CR) with the use of a combination chemotherapy (intermediate-dose Ara-C, vindesine, mitoxantrone, cyclophosphamide, prednisolone and methotrexate).…”
Section: Discussionsupporting
confidence: 65%
“…Several studies have indeed demonstrated that the in vitro sensitivity to cytarabine of AML cells could be enhanced by preincubation with granulocyte colony-stimulating factor (G-CSF) and/or with granulocyte -macrophage colony-stimulating factor (GM-CSF) (Butturini et al, 1990;Bai et al, 1999). Clinically, pretreatment with G-CSF (as in the FLAG regimen, which is a combination therapy of fludarabine, cytarabine, and G-CSF), seems to be effective and well tolerated in the treatment of poorrisk AML patients (Montillo et al, 1998;Jackson et al, 2001). The efficacy of this therapy, however, has not yet been determined in a controlled, randomised clinical study.…”
Section: Discussionmentioning
confidence: 99%
“…1 GCLAC was similar to the FLAG regimen (fludarabine, cytarabine (ara-C) and G-CSF priming), [2][3][4][5][6][7][8][9] with clofarabine substituted for fludarabine. Metabolism of both compounds to their triphosphates may increase synthesis of the triphosphate of ara-C (ara-CTP).…”
Section: Introductionmentioning
confidence: 99%